Roe v. Wade - Hillstrom, Laurie Collier, 1965- (Detroit, MI : Omnigraphics, 2008)
"Explores the history of abortion in America, describing the Roe v. Wade case, explaining the decision and its implications, and examining the continuing debate over abortion rights and its impact on American society and politics. Features include a narrative overview, biographical profiles, primary source documents, detailed chronology, glossary, annotated sources for further study, bibliography, and index"--Provided by publisher.
The early history of abortion -- The rise of the feminist and abortion-reform movements -- Roe v. Wade -- The landmark decision and its implications -- The court limits Roe's reach -- Roe survives a major challenge -- Roe's legacy : the battle continues.
Includes bibliographical references (p. 235-240) and index.
Includes bibliographical references and index.
Keywords: Abortion -- United States -- History; Abortion -- Law and legislation -- United States; Abortion -- Moral and ethical aspects